Exemplary clinical models of teacher education - Helfrich, Sara R.; Hartman, Sara Lohrman (Advances in teacher education., 2023)
"Across settings, teacher education programs utilize innovative practices to prepare teacher candidates, yet rarely is this work shared in a way that is accessible to stakeholders. This book presents exemplary models utilized by universities in a variety of settings, with the objective of sharing with readers a sampling of research-based teacher preparation models that are currently in place at accredited universities and colleges across the country, in an effort to help others that are developing or redesigning their programs. Authors of the included chapters focused on the setting in which their college/university is located. Location impacts every aspect of a clinical model of teacher preparation, including the number and proximity of placements that are available for teacher candidates, access to resources, and diversity of experiences. The authors, in describing their clinical model, address how their location impacts their model, sharing information about the resources to which they have access, how they make use of available resources in potentially unique ways, as well as how they overcome a lack of resources to provide a meaningful and diverse experience for their candidates. Readers will be able to use this book to learn more about how similar colleges/universities are embracing their locations and resources to further the learning of their candidates and to implement these ideas within their own programs. All those involved in teacher preparation - state-level policy makers, university and P-12 administrators, and educators who bridge university and school settings to work together to prepare teacher candidates - will benefit from this book. It can serve as a resource for these individuals to help inform them of how universities and colleges across the country are implementing a clinically-based teacher preparation program so that they have a model for creating, implementing, assessing, and maintaining their own program. Additionally, teacher education faculty and staff may utilize it for help with self-studies and accreditation purposes, and as a text to use within courses in principal and/or superintendent preparatory programs"--